Wilkie Collins and the politics of adaptation on the Victorian stage - Laurella, R (2020)
As the sensation novel was reclaimed by literary critics and cultural historians as a legitimate site of academic inquiry in the mid-twentieth century, Wilkie Collins’s canonical works became the topic of much scholarly interest. His works have consistently been identified as the locus of a plethora of narrative and formal innovations that have irrevocably shaped how we understand both the Victorian novel and its successors. As this thesis will demonstrate, however, Collins’s writing for the stage – in particular dramatising his own novels – had a more significant influence on his career than has previously been acknowledged. By reading those dramatic works alongside their novelistic versions and against the landscape of Victorian theatre, this thesis refines our understanding of this canonical novelist while also demonstrating the interrelatedness of the novel and the stage for Victorian readers, writers, audiences, and critics.